PROSES PENULISAN LONTAR TUTUR AJI SARASWATI KARYA IDA BAGUS OKA MANOBHAWA DALAM FOTOGRAFI STORY - Permana, I Kadek Dwiki Krishna; Raharjo, Anis; Pramana, I Made Bayu (Retina Jurnal Fotografi, 2022)
When technology is increasingly sophisticated and information is very easy to obtain, for example e-books via the internet. Writing using lontar that has been known before is replaced by books and e-books. In connection with the work practice of the MBKM activity program at the Janahita Mandala Ubud Foundation. The author documents photos of the program activities, namely Sarasastra and lontar conservation. In carrying out activities, the author realizes the lack of interest and information from the public regarding lontar so that there is a lack of interest in preserving cultural heritage. Therefore, the author made a photography story entitled "The Process of Writing Lontar Tutur Aji Saraswati by Ida Bagus Oka Manobhawa in Story Photography" which illustrates the process of writing a papyrus script to finish. The photoshoot begins with a photo of the pengawi house, process of writing the lontar, and finally the result is a lontar. The author conducted a literature study through books, journals, and websites as well as observations regarding the writing of lontar and conducted direct interviews. The author uses EDFAT theory and aesthetic theory in the creation of photo works. In the process of shooting, the author applies several photography techniques, namely motion blur, and using sunlight and external flash. It is hoped that the results of the research photos can be seen by the public so that they are interested in contributing to the preservation of cultural heritage, so that time is not lost in the rapid development of technology and information.